Porcine Small Intestine Submucosal Grafts for Post‐tumor Resection Orbital Reconstruction. (23rd August 2013) - Phillips, James D.; Riley, Kristen O.; Woodworth, Bradford A.
Abstract : Objectives: With sinonasal malignancy, removal of the medial orbital wall for tumor involvement is required to obtain complete oncologic resection. However, orbital fat herniation can produce significant morbidity, including enophthalmos and diplopia. The purpose of the current study was to evaluate outcomes following use of porcine small intestine submucosa (SIS) grafts for orbital reconstruction following extirpation of sinonasal malignancies. Methods: Review of prospectively collected data regarding orbital reconstruction using SIS was performed. Demographics, tumor histology, size of orbital defect, adjuvant treatment, clinical status, and complications were recorded. Results: Seventeen patients (average age 58, range 27‐82) had SIS grafting of the medial orbital wall over a five year period at our tertiary academic institution. Average orbital wall defect size was 1.6 x 2.1 cm (height vs. length). Tumor histopathology included esthesioneuroblastoma (n=5), squamous cell carcinoma (n=4), adenocarcinoma (n=2), sinonasal undifferentiated carcinoma (n=2), melanoma (n=3), and neuroendocrine carcinoma (n=1). Surgical goals were curative intent in all patients. Ten patients had postoperative radiation therapy, while 5 individuals had surgical extirpation following neoadjuvant chemotherapy and radiation. All patients had complete locoregional control at last clinical follow‐up (average 16 months, range 2‐54), although three patients developed distant metastases. The only orbital complications noted were enophthalmos (n=1), periorbital cellulitis (n=1), and orbital wall crusting (n=1). Conclusions: SIS reconstruction of orbital wall defects was effective in the current series of patients with only one patient developing noticeable enophthalmos and a low incidence of surgical complications.